Buyer Beware, or Buyer Unaware? Examining the Correlates of Consumer Fraud Victimization Acknowledgment in the United States - Maher, Cooper A. (Crime & delinquency, 2025)
Victims’ acknowledgment of their experiences as criminal events is a crucial first step to any criminal justice involvement. Works examining the topic have identified several factors associated with acknowledgment, including the seriousness of the offense, repeat victimization, help-seeking behaviors, and distress. Despite this, works examining acknowledgment have been restricted to interpersonal offenses, limiting understandings of whether correlates of acknowledgment can apply in other specific domains, such as for consumer fraud. Using a sample of consumer fraud victims from the National Crime Victimization Survey Supplemental Fraud Survey (n = 411), findings indicate that distress and help-seeking increased odds of acknowledgment, while repeat victimization was not associated with acknowledgment. Findings are discussed in light of future directions for research and policy.